2012
DOI: 10.1017/s1473550412000304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-energy astrophysical events on habitable planets

Abstract: With the possible exception of meteor impacts, high-energy astrophysical events such as supernovae, gamma-ray bursts (GRB) and flares are usually not taken into account for biological and evolutionary studies due to their low rates of occurrence. We show that a class of these events may occur at distances and time scales in which their biological effects are non-negligible, maybe more frequent than the impacts of large asteroids. We review the effects of four transient astrophysical sources of ionizing radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…The second aspect that we highlight concerns the effect of planetary magnetic fields in regulating the amount of cosmic rays that reach the surface. This is particularly relevant since high-energy radiation can drive the radiolysis (decomposition via radiation) of complex biomolecules (Dartnell, 2011;Horvath and Galante, 2012). It is wellknown that the planet's magnetospheric shielding (for deflecting charged particles) influences the amount of radiation that reaches the surface (Grießmeier et al, 2009), but more recent studies have revealed that the dependence on the magnetic moment M p is very sensitive to the atmospheric column density (Atri et al, 2013).…”
Section: A Planetary Magnetospheresmentioning
confidence: 99%
“…The second aspect that we highlight concerns the effect of planetary magnetic fields in regulating the amount of cosmic rays that reach the surface. This is particularly relevant since high-energy radiation can drive the radiolysis (decomposition via radiation) of complex biomolecules (Dartnell, 2011;Horvath and Galante, 2012). It is wellknown that the planet's magnetospheric shielding (for deflecting charged particles) influences the amount of radiation that reaches the surface (Grießmeier et al, 2009), but more recent studies have revealed that the dependence on the magnetic moment M p is very sensitive to the atmospheric column density (Atri et al, 2013).…”
Section: A Planetary Magnetospheresmentioning
confidence: 99%
“…The predicted effects of hard photon radiation on Earth include temporarily elevated levels of cosmogenic isotopes such as 14 C, 10 Be and 36 Cl, ionization of N species in the atmosphere, depletion of the ozone layer, increased UV radiation at the Earth's surface and delivery of fixed N to the Earth's surface. There is a rich literature describing these potential effects (Terry and Tucker, 1968; Ruderman, 1974; Clark et al ., 1977; Rood et al ., 1979; Thorsett, 1995; Scalo and Wheeler, 2002; Gehrels et al ., 2003; Melott et al ., 2003, 2005; Thomas et al ., 2005; Galante and Horvath, 2007; Martín et al ., 2009; Thomas, 2009; Horvath and Galante, 2012; Gowanlock, 2016). If sufficiently intense, the radiation events can also affect other solar system atmospheres and surfaces (Duggan et al ., 2001; Scalo and Wheeler, 2002; Fox et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Supernovae have been considered as a possible cause of terrestrial extinctions and lesser events for a long time, at least since Schindewolf (1954). Later work was done by Ruderman (1974); Whitten et al (1976); Gehrels et al (2003); Horvath and Galante (2012); ; Melott et al (2015Melott et al ( , 2017. Due to recent detections, there have been new computations which shed light on the effects of events at moderate distances, such as 150 to 300 light years.…”
Section: Introductionmentioning
confidence: 99%